Analysis on a hydrophobic hollow-fiber membrane absorber and experimental observations of CO2 removal by enhanced absorption - Chun, MS; Lee, KH (MARCEL DEKKER INC, 1997)
In this paper an extended analysis on a hollow-fiber membrane absorber is conducted for CO2 removal from flue gases. A rigorous model of gas-liquid mass transfer is developed on both narrow channels in and around the hollow fibers, including the gas absorption occurring from the reaction between CO2 and aqueous K2CO3 absorbent. CO2 concentration profiles can be obtained regardless of the placement of the flowing absorbent. Experimental observations of the CO2 concentration in both the reject and permeate outlets compared with theoretical prediction allow us to understand the influence of flow rates of feed gas as well as absorbent on CO2 absorption. For the flowing K2CO3 absorbent a kinetic constant can be chosen which will provide the best possible agreement between experiment and reactive model prediction. This fact emphasizes that the pseudofirst-order kinetic can be employed to describe the facilitation effect. The overall mass transfer coefficients were determined from the experimentally observed concentration changes. The CO2 permeation flux was found to be enhanced as the K2CO3 concentration was increased, suggesting that CO2 removal is entirely controlled by the reaction. The enhanced selectivity factor for CO2/N-2, which decreases with increasing absorbent flow rate, reached as high as 1200 with 15 wt% K2CO3 absorbent.
Keywords: GAS-LIQUID CONTACTORS; PLANT FLUE-GAS; MASS-TRANSFER; FACILITATED TRANSPORT; CARBON DIOXIDE; MODULES; SEPARATION